Penerapan Pembelajaran Bioentrepreneurship untuk Meningkatkan Life Skills dan Minat Wirausaha Siswa SMK - Deden Ibnu Aqil; Adeng Hudaya; Zainal Arifin (Universitas Kanjuruhan Malang, 2019)
The application of learning in schools emphasizes students get knowledge from their experience directly. Most of the graduates of vocational students do not go to college but the desire or interest of students for entrepreneurship is very low, therefore schools must equip students with life skills to prepare them to face life after they graduate from school. The problem of this study is how to approach the application of biointrenrenship learning to vocational students to improve life skills and interest in student entrepreneurship. This research is a research development (R & D). Development of learning oriented bioentrepreneurship and tested experimental class. Data was taken by observation, questionnaire and test. Data analysis method used descriptive percentage of life skills scores and questionnaires then analyzed by paired samples test. From the results of the study, there was an increase in interest in entrepreneurship and life skills of students before and after the application of bio-entrepreneurship learning.